Community Resilience and Political Behavior: The Case of Disaster-Resilient Village in Banyuwangi During COVID-19 - Fahadayna, Adhi Cahya; Alfian, Faqih; Bachtiar, Rizqi (Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to explain the Banyuwangi people's perception of the government's institutional capacity in mitigating COVID-19 and the quality of democracy seen from the government's institutional capacity in the electoral political agenda. These focuses will be answered through analysis using the conceptual framework of community resilience and political behavior as a benchmark for liberal good governance. The results show that the disaster governance in seven disaster-resilient villages in Banyuwangi indicates dissatisfaction among several citizens regarding the aid programs. There are differences in information obtained between the government and the community regarding the distribution of goods and services during the COVID-19 pandemic, though some others are satisfied with the government. Consequently, while disaster governance shapes the civils' perception toward the current regent, Ipuk Fiestiandani, it also affects their political behavior toward the incumbent in the 2024 regional election.